2019
DOI: 10.12911/22998993/99734
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of an Environment on the Content of Macro- and Microelements in the Tanacetum vulgare

Abstract: Tansy (Tanacetum vulgare L.) grows in moderate area of the northern hemisphere, in Poland -its range covers the whole country. It appears on the farm wastelands, by roadsides, on enbankments, river banks, forest lips and in open spaces. The present paper has faced the challenge of defining the influence of the environmental conditions on the mineral composition of Tanacetum vulgare leaves. The plants were picked in the blooming period from May to September 2017 in 12 natural environments of their growth and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The extraction module was 1:40 for 15 cycles over a period of up to 8 h. The formic and trifluoroacetic (TFA) acids were used to acidify the medium. The NaOH and NH 4 OH solutions were used for alkalization [ 16 ]. According to the literature, the elevated temperature used in the Soxhlet method destroys non-heat-resistant substances [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction module was 1:40 for 15 cycles over a period of up to 8 h. The formic and trifluoroacetic (TFA) acids were used to acidify the medium. The NaOH and NH 4 OH solutions were used for alkalization [ 16 ]. According to the literature, the elevated temperature used in the Soxhlet method destroys non-heat-resistant substances [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was demonstrated that such compounds as β-thujone, camphor, and chrysanthenium acetate are the main components of T. vulgare essential oil. These substances were found in the essential oil of T. vulgare from 11 different localities in different parts of the world [ 16 , 17 ]. It was noted that the leaves and inflorescences of the T. vulgare plant synthesize the same amount of essential oil, but of different composition.…”
Section: Introductionmentioning
confidence: 99%
“…Tansy (Tanacetum vulgare L.) is a perennial from the aster family (Asteraceae) which is widespread in Poland. It is found mostly on agricultural waste grounds, waysides, river banks and on open spaces [Konieczny and Ślęzak 2019]. Tansy flower heads and herbs are used in medicine.…”
Section: Introductionmentioning
confidence: 99%